Development of a Multilocus Sequence Typing Method for Analysis of Listeria monocytogenes Clones - Salcedo, C. (American Society for Microbiology, 2003)
This study is a first step in the development of multilocus sequence typing (MLST) method for Listeria monocytogenes. Nine housekeeping genes were analyzed in a set of 62 strains isolated from different sources and geographic locations in Spain. These strains were previously characterized by pulsed-field gel electrophoresis (PFGE). Because of low diversity, two loci were discarded from the study. The sequence analysis of the seven remaining genes showed 29 different allelic combinations, with 22 of them represented by only one strain. The results of this sequence analysis were generally consistent with those of PFGE. Because MLST allows the easy comparison and exchange of results obtained in different laboratories, the future application of this new molecular method could be a useful tool for the listeriosis surveillance systems that will allow the identification and distribution of analysis of L. monocytogenes clones in the environment.